Appraisal Theory applied to the wine tasting sheet in English and Spanish - Bozena Wislocka Breit (Ibérica, Revista de la Asociación Europea de Lenguas para Fines Específicos, 2014)
The main goal of this study is the application of Appraisal Theory (Martin & White, 2005) developed in the framework of Systemic Functional Linguistics to wine tasting sheets. Firstly, whether this text type meets the defining requirements specified by Swales (1990) for the discursive genre will be verified. 110 tasting sheets in Spanish and English extracted from the Internet have been grouped into four corpora corresponding to the country of origin of the wine: Spain, Australia, California and New Zealand. An analysis undertaken with WordSmith Tools has demonstrated the positive polarization of all the texts and the existence of cultural differences reflected in the use of fruit-related terms, adjectives oenological terms and “oenological culturemes” (Wislocka Breit, 2012). An unforeseen result of the study was the strong contrast observed between the free and literary manner of the English and the concise style of Spanish tasting sheets.